Réponses

2012-09-30T12:31:58+02:00

(3x+1) (6x-9) - (2x -3)²

= 18x² - 27x + 6x - 9 - (4x² - 12x + 9)

= 18x² - 27x + 6x - 9 - 4x² + 12x - 9

= 18x² - 4x² - 27x + 12x + 6x - 9 - 9

= 14x² -9x - 18

 

x = (3/2)

14(3/2)² -9(3/2) - 18

= 63/2 - 27/2 - 36/2

= 0

 

x= (-6/7)

14(-6/7)² -9(-6/7) - 18

= 14*36/49 + 378/49 - 126/49

= 504 + 378 - 126 / 49

= 756/49

= 108/7

2012-09-30T12:32:25+02:00

1) il suffit de dévelloper :

(3x+1)(6x-9)-(2x-3)² =18x²-27x+6x-9-(4x²-2*6x+9)

                               = 18x²+27x+6x-9-4x²+12x-9

                               = 14x²-9x-18

 

2) il faut remplacer x dans A :

 

  x = 3/2  :  14*(3/2)²-6*(3/2)-18  = 4.5

 

 

x = -6/7   : 14*(-6/7)²-6*(-6/7)-18 = -24